AB0611 Leflunomide in rheumatoid arthritis: Efficacy and safety analysis. Loading dose assessment. (23rd January 2014) - Clavaguera, T.; Reyner, P.; Valls, R.; Costa, R.; Codina, O.; Valls, M.; Sala, M.; De Cendra, E.; Ruelle, C.; Sánchez, I.; Coderch, J.; Rodríguez, M.C.
Abstract : Background: Leflunomide (LFN) is used as a DMARD in the treatment of rheumatoid arthritis (RA). The consensus of using loading dose (LD) has not yet been established and it has only been analysed in scarce studies. Objectives: To assess efficacy and safety of patients who were treated with LFN because of RA. We also analyse the effect of the LD and if treatment with prior DMARD changed the clinical response. Methods: We conducted an observational post-authorization, prospective, multicentre study under condition of daily clinical practice in patients with active RA receiving LFN. Our patients were recruited from June 2009 to September 2010 from 5 outpatients' rheumatology services in Girona (Spain). Inclusion criteria were: age >18 years, diagnosis of RA based on ACR 1987 criteria, active RA (DAS 28 ≥3.2) and indication of treatment according to the consensus of Spanish Society. Exclusion criteria: specific contraindications of LFN, failure to a correct follow-up, pre-treatment with LFN or biological therapy. Study variables were: 1) dependent variables: efficacy (DAS 28 and EULAR response criteria), safety (variable drop-outs and side effects), 2) independent variables: age, sex, RF, ACPA, LD, disease associated variables, previous therapies and laboratory data. Assessment was performed at 4, 8, 12 and 24 weeks. Data evaluation and statistical analysis (SPSS-18.0 software package): 1) Univariate analysis: frequencies and main statistical. 2) Bivariate descriptive analysis using χ 2 test, Fisher's exact test and t-Student with a significance level of 5%. Results: 76 patients were included. 64 (84.2%) were women. The mean age was: 54 yrs. (range 29-80). 37 (48.9%) received LD (100mg/day for 3 days). 30 (39.5%) hadn't received any DMARD prior to LFN but 38 (50%) had been previously treated with MTX. Population characteristics (median [range]) were: mean duration of disease 24 months (4-420m.), 24 (31.6%) had erosions, 40 (52.6%) RF+, 39 (51, %) ACPA +, TJC 7 (1-25), SJC 5 (0-19), patient VAS 60 (10-100), ESR 25.5 mm/1st h (1-66), CRP 6.40 (0-50)mg/L, DAS 28 5.21 (3, 22-6, 79) and HAQ 1, 125 (0 to 2.750). Remission rate at 24 week (DAS 28 <1.6): 22.8%, LDAs 28 (DAS <3.2): 7.01%. According to the EULAR response criteria, our results were: 16 patients (28%) none, 25 (43.9%) moderate and 16 (28%) good response. Our dropout rate was 18.4% (4.1% to 4.1% lack of efficacy and side effects, respectively). In bivariate analysis, we didn't find any significant difference in efficacy nor safety between patients receiving or not LD. Furthermore, we didn't also observe a faster effect in LD group. Finally, there were no differences between patients who LFN was the first DMARD used and those who received a prior therapy with MTX. Conclusions: Our results do not greatly differ from those reported in the literature. Loading dose has no advantages in RA patients treated with LFN. These results had not been influenced by a prior therapy with MTX. Although, studies with a greater sample size were needed, probably, the use of the LD should be definitely excluded from the guidelines and consensus of RA therapy. Disclosure of Interest: None Declared